The combined application of quality function deployment and pareto analysis for hotel services improvement (2008)
This paper discusses the combined application of Quality Function Deployment (QFD) and Pareto Analysis (PA) to hotel services. This paper improves the current quality management practices in a case study hotel. This results into increased customer patronage and improved hotel profit margin. PA is applied as a prioritisation tool for the purpose of financial investment decision. The study may be applicable to other hotels. It could also significantly affect the goodwill of the organisation as well as its profit margin. This paper is new, in that it appears to be the first application of Pareto cum QFD principles in hotel services, and a new way of prioritisation and quality improvement in hotels systems